THE APPLICATION OF ROLLING BALL MEDIA TO IMPROVE ARABIC VOCABULARY MASTERY OF SEVENTH-GRADE STUDENTS - Sitra Amalia S.; Fadli; Mustafa; Naidin Syamsuddin (Universitas Islam Negeri Palopo, 2025)
This study aimed to describe the implementation of the Rolling Ball learning media and to examine its effectiveness in improving the Arabic vocabulary mastery of seventh-grade students at MTs DDI 1 Palopo. The study employed a qualitative approach using Classroom Action Research based on the Kemmis and McTaggart model. The research was conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The participants were 22 seventh-grade students. Data were collected through observation, tests, documentation, and field notes, while the data were analyzed descriptively based on the observation results and students' learning outcomes in each cycle. The findings revealed that the implementation of the Rolling Ball learning media significantly improved both the learning process and students' Arabic vocabulary mastery. The students' mean score increased from 32.09 in the pre-cycle to 71.55 in Cycle I and further improved to 81.41 in Cycle II. Likewise, the classical learning mastery improved from 0% in the pre-cycle to 63.6% in Cycle I and reached 100% in Cycle II. In addition to improving learning outcomes, the Rolling Ball media enhanced students' learning motivation, active participation, self-confidence, and collaborative skills throughout the instructional process. Therefore, the Rolling Ball learning media can be considered an effective alternative instructional medium for improving Arabic vocabulary mastery at the junior secondary Islamic school level.